A strategy to improve livelihoods and restore degraded lands in Haiti - Guimarães, E.; Zandstra, Andre (2013)
CIAT - International Center for Tropical Agriculture. Achieving Sustainable Agricultural Production in Haiti. In collaboration with international and local partners to assist with Haiti’s severe food production constraints in three major areas: